New chronological evidence reveals a continuously inhabited Neolithic–historical settlement in south China - Jin, Jianhui; Li, Fusheng; Ling, Zhiyong; Li, Zhizhong (Palaeogeography, palaeoclimatology, palaeoecology, 2022)
The Xindian Ancient City (XAC) site is the most complete and frequently excavated urban site in the lower reaches of the Minjiang River. Archaeological and chronological research of this area helps clarify the history of human activity at the site and restore the geographical background of the ethnic minority regimes who lived in the coastal areas of south China during the Eastern Zhou dynasty and the related influence on regional civilisation. Dating results suggest that the site was built during the Spring and Autumn and Warring States periods (3.2–2.4 thousand years ago), which can reasonably explain the presence of relics from the Warring States period on and within the wall. Our dating results are also consistent with the late Neolithic stone tools and pottery fragments found in the area, suggesting that the site was an ideal settlement before castles were constructed. Based on the spatial distribution of the Neolithic sites and Holocene transgression records in the Fuzhou Basin, it was found that coastline advance and retreat were the main factors affecting the paleo-human activity in the Fuzhou Basin during the late Neolithic period. Previous studies showed that the seawater gradually withdrew from the basin around 2 ka BP. Before this, humans mainly lived in the crescent-shaped area on the west side of the Fuzhou Basin, close to the ancient coastline. Based on existing archaeological results and chronological data, it can be shown that the lower reaches of the Minjiang River, where Fujian Province's capital is located, has long been the centre of ancient human activity in the coastal areas of south China, with a civilisation history of 6–4 ka and a city construction history of at least 2.9 ka. •It is the earliest urban site in the lower reaches of the Minjiang River, China.•The site was a continuously inhabited Neolithic−historical settlement.•The geomorphic pattern led to long-term human activity in the coastal estuaries.•Sea level change can control the spatial distribution of sites in the estuary area.